Strategi Inovatif Berbasis Digital dalam Kegiatan Kepramukaan Terhadap Pengembangan Karakter Murid Madrasah Aliyah Cikande Bandung Barat - Siti Hodijah; Jajang Hendar Hendrawan; Neneng Tripuspita (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study is motivated by the importance of strengthening character education in the digital era, which requires innovation in extracurricular activities, particularly scouting. This research aims to analyze the effect of digital-based innovative strategies in scouting activities on students’ character development, including responsibility, discipline, and independence at Madrasah Aliyah Cikande Bandung Barat. The study employed a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to the research sample and analyzed using simple regression, hypothesis testing, and coefficient of determination. The results indicate that digital-based innovative strategies have a significant effect on students’ character development, both partially and simultaneously. The integration of technology in scouting activities enhances student engagement, motivation, and learning experiences, making them more interactive and relevant to current developments. Furthermore, this strategy contributes to improving students’ digital literacy and 21st-century skills. Therefore, the implementation of digital-based innovative strategies in scouting activities can serve as an effective alternative for strengthening character education in madrasah contexts.